ANALISIS FRAMING BERITA TAWURAN ANTAR PELAJAR DI HARIAN KOMPAS - Herieningsih, Sri Widowati (JURNAL ILMU SOSIAL, 2014)
Student brawls occur continuously in various cities, especially in theÂ  Jakarta, the attention of many people, and did not escape the attention of the media. Framing Kompas is a mayor concern in this study.The study conducted by taking a sample 0f 37 news, between 2008 to 2012. The paradigm used is the paradigm of constructivism. The method used is the analysis of the model Entman framing.The results that the Kompas student brawls see that the problem is complexs issue, and not ordinary deliguency, but it leads to crime, a form of deviance. Student brawls, agroup behavior, and other problems caused by unclear, revenge hereditary, in solidarity with friends, as well as maintain the good name of the school, violence derived from the senior students to yunior. Recommendation are offfered to prevent and fight is, sanction, both preventive and repressive, conducted formal and nonformal.